2014
DOI: 10.1016/j.neurobiolaging.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of APOE genotype and testosterone on episodic memory in middle-aged men

Abstract: Age-related changes in testosterone are believed to be a key component of the processes that contribute to cognitive aging in men. The APOE-ε4 allele may interact with testosterone and moderate the hormone’s association with cognition. The goals of the present study were to examine the degree to which free testosterone is associated with episodic memory in a community-based sample of middle-aged men, and examine the potential interaction between free testosterone and the APOE-ε4 allele. Data were utilized from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 101 publications
3
20
0
Order By: Relevance
“…These results highlight the need for additional studies of the E4 gene by environmental interactions, especially in various nonindustrial environments, and for focusing on the neurobiology of middle age in addition to older age and the need to take a life‐course perspective (55, 56). Other studies have found evidence of protective interactions between E4 alleles, cognitive function, and a host of other phenotypic characteristics, including testosterone (57), estrogen (58), and physical activity (59). Considered together, the evidence suggests that the impacts of the E4 allele are not always deleterious and may be adaptive and beneficial in some populations with a high infectious burden.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the need for additional studies of the E4 gene by environmental interactions, especially in various nonindustrial environments, and for focusing on the neurobiology of middle age in addition to older age and the need to take a life‐course perspective (55, 56). Other studies have found evidence of protective interactions between E4 alleles, cognitive function, and a host of other phenotypic characteristics, including testosterone (57), estrogen (58), and physical activity (59). Considered together, the evidence suggests that the impacts of the E4 allele are not always deleterious and may be adaptive and beneficial in some populations with a high infectious burden.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence for the APOE allele to affect thyroid status in males. On the other hand, in middle-aged men being ε4 allele carriers, the free testosterone level was positively associated with verbal episodic memory performance (story recall), whereas no association was observed in ε4 allele noncarriers [43]. Also individuals with both low free testosterone levels and at least one copy of the ε4 allele had smaller hippocampal volumes than men who had none or only one of these risk factors [44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a smaller hippocampus is evidenced in middle-aged men with lower serum testosterone levels possessing an APOE4 allele (Panizzon et al, 2010). Further, better verbal memory in middleaged men with APOE4 was found in those with higher levels of testosterone (Panizzon et al, 2014). Increased amyloid burden was associated with decreased testosterone levels in men with mild cognitive impairment (MCI) carrying at least one APOE4 allele (Verdile et al, 2014).…”
Section: Androgens and Neurogenesis: Potential Implications For Cognimentioning
confidence: 99%